2019
DOI: 10.3390/ma12172812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonation on Abrasion Resistance of Alkali-Activated Slag with Various Activators

Abstract: The effect of carbonation on the abrasion resistance of alkali-activated slag (AAS) was investigated. Various activator sets were selected for synthesizing AAS specimens, and the compressive strength was measured before and after carbonation. The abrasion resistance of the specimens was measured in accordance with the ASTM C944 test method. The relationship between the mass loss caused by abrasion and compressive strength was analyzed to understand the effect of matrix strength on abrasion resistance. Test res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Cho et al [ 12 ] investigated the effect of cations on the sulfate resistance of alkali-activated fly ash and slag blended mortar, concluding that this binder tends to experience deleterious damage when magnesium sulfate solution is used. Kim et al [ 13 ] reported that carbonation leads to a substantial decrease in the abrasion resistance of alkali-activated slag cements. Alkali-activated binders often exhibit a large extent of drying shrinkage, therefore Son et al [ 14 ] explored a means of reducing the drying shrinkage by incorporating CaSO 4 and investigating its effect on the pore structure.…”
mentioning
confidence: 99%
“…Cho et al [ 12 ] investigated the effect of cations on the sulfate resistance of alkali-activated fly ash and slag blended mortar, concluding that this binder tends to experience deleterious damage when magnesium sulfate solution is used. Kim et al [ 13 ] reported that carbonation leads to a substantial decrease in the abrasion resistance of alkali-activated slag cements. Alkali-activated binders often exhibit a large extent of drying shrinkage, therefore Son et al [ 14 ] explored a means of reducing the drying shrinkage by incorporating CaSO 4 and investigating its effect on the pore structure.…”
mentioning
confidence: 99%